Learners’ processes during pre-task planning and Working Memory Capacity - Maria da Gloria Tavares (Ilha do Desterro)
The present study is part of a larger scale research (Guará-Tavares, 2011, 2013) that investigates the relationship among working memory capacity, pre-task planning, and L2 speech performance. The aim of the study was to analyze 1) what processes learners engage during pre-task planning, and 2) whether higher and lower working memory spans engage in different processes during pre-task planning. Learners’ processes were accessed by means of think aloud protocols and a retrospective interview. Working memory capacity was measured by the Speaking Span Test. Results show that learners engage mainly in organization of ideas, rehearsal, lexical searches, and monitoring.. Moreover, higher spans employ significantly more metacognitive strategies during planning when compared to lower spans.